The timeless exemplarity of classical values: Emil Staiger in the 1930s–1950s - Angelov, Angel (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2025)
Staiger’s publications from the 1930s and 1950s are analysed in order to substantiate what the anti-modern orientation of his concept consists of. Staiger’s concept is placed in relation to the notion of “engaged literature”. Staiger’s position is discussed in two lectures from 1937, the subject of which is German-Swiss friendship in spiritual life. I find that the work of Adalbert Stifter is important to Staiger because of the combination of artistic form and morality, order and artistry. I argue that it is possible to match Staiger’s interpretations with a basic position that was being developed at the same time in the theory of socialist realism. The conclusion is that it is the ahistorical understanding of the classical that can be used to support a totalitarian social order whose goal is to perpetuate its power and suspend history.